An Investigation on Soil Amplification through Site Factors Used in Seismic Design Codes - Hayri Baytan Ozmen (Advances in Civil Engineering)
This article aims to investigate the site amplification through site coefficients given in the seismic codes. A set of 84 ground motion records in a base rock form and targeted to have different frequency contents was formed. The surface forms of these records altered by 100 different soil conditions were determined. Using this set of 8400 ground motion records, site amplification phenomenon is examined. After a PGA of 0.3 g, ground motions have similar behaviour in terms of short period amplification. Numerical figures as average and with a safety level of 84% for the SS and S1 site coefficients were given and compared with the code which are observed to be unconservative for stiff soils and too conservative for soft soils. Linking SS with a VS value of 600 m/s and S1 with a VS value of 120 m/s seems to be useful to understand some amplification behaviours. The variability of ZB and ZC site classes for short period site coefficient and ZE and ZD site classes for midperiod site coefficient seems to be greater when compared to others.